Protective effects of curcumin in APPswe transfected SH-SY5Y cells - Yin, Wenke; Zhang, Xiong; Li, Yu (Neural regeneration research, 2012)
The APPswe plasmid was transfected into the neuroblastoma cell line SH-SY5Y to establish a cell model of Alzheimer＇s disease. Graded concentration and time course experiments demonstrate that curcumin significantly upregulates phosphatidylinositol 3-kinase （PI3K）, Akt, nuclear factor E2-related factor-2 （Nrf2）, heme oxygenase 1 and ferritin expression, and that it significantly downregulates heme oxygenase 2, reactive oxygen species and amyloid-beta 40/42 expression. These effects of curcumin on PI3K, Akt and Nrf2 were blocked by LY294002 （PI3k inhibitor） and NF-E2-related factor-2 siRNA. The results indicate that the cytoprotection conferred by curcumin on APPswe transfected SH-SY5Y cells is mediated by its ability to regulate the balance between heme oxygenase 1 and 2 via the PI3K/Akt/Nrf2 intracellular signaling pathway.